Popravljanje in odpravljanje napak v procesu usvajanja tujega jezika - Žugelj, Nataša (Vestnik za tuje jezike, 2011)
This article considers the attitude of teachers and linguists towards the students' errors during the process of foreign language acquisition. The unfavourable attitude has changed, so that analysis of errors and its categorisation have turned errors into a valuable device used in the classroom. This new approach to errors encourages the students to think about their errors and the functioning of the language system which they want to acquire. The teacher who tries to improve the students' language competence, has to have good theoretical knowledge and a great deal of patience, but above all has to be able to choose the most appropriate moment and way to treat the error, which is a very long process demanding a very active collaboration between a teacher and a student.
Keywords: norme; tuji jeziki; napake; popravljanje napak; didactic method; didaktika; metodika